SURAT WASIAT SEBAGAI PENGHINDAR CAMPURTANGAN PEMERINTAH DI AMERIKA SERIKAT BAGAIAN SELATAN - Tatit Hariyanti (Jurnal Dinamika Hukum, 2012)
Southerners are famous for their exaltation  of their honor and the sanctity of  their private property. Any obstacles in  the ownership and the management of their private property will be regarded as a form of interference and will be eliminated or at least minimalized.   Intestacy laws  and death taxes are regarded as  the government’ s interference. Intestacy laws are applied when there is no valid last will and testament. The taxes  will be high or low depending of  the smartness in utilizing the offered deduction through last will and testament.  Key words:    sanctity of private property, honor, intestacy laws, taxes, interference, last will and testament.